Development of a lubricant-free revolving vane compressor - Aw, Kuan Thai (2017)
The concept of a lubricant-free compressor is attractive as it would be unconstrained by orientation and therefore applicable for portable small-scale cooling and heating applications. With inherently low friction losses, the revolving vane (RV) mechanism has the potential for development into such a compressor. A new vane and vane slot design is proposed to reduce the number of rubbing components and the self-lubricating polyetheretherketone (PEEK) material is used for fabricating these rubbing components of the compressor. Comprehensive mathematical models are developed for the new compressor design with considerations for heat transfer, internal leakage and vibration. The compressor prototype has seizure and severe leakage issues due to poor machining accuracy. Nevertheless, measurements from testing of the compressor prototype were used to validate the thermodynamics model and had good agreement with ±15% errors. On the other hand, validation of the dynamics model was achieved with measurements from a previous work on a RV air expander prototype. The measurements showed that the vibration of the RV mechanism is bimodal due to the presence of the clearance gap between the vane and vane slot. This lays out the groundwork for future development of the lubricant-free RV compressor.